Femtosecond timing-jitter between photo-cathode laser and ultra-short electron bunches by means of hybrid compression. (12th August 2016) - Pompili, R; Anania, M P; Bellaveglia, M; Biagioni, A; Castorina, G; Chiadroni, E; Cianchi, A; Croia, M; Giovenale, D Di; Ferrario, M; Filippi, F; Gallo, A; et al.
Abstract: The generation of ultra-short electron bunches with ultra-low timing-jitter relative to the photo-cathode (PC) laser has been experimentally proved for the first time at the SPARC_LAB test-facility (INFN-LNF, Frascati) exploiting a two-stage hybrid compression scheme. The first stage employs RF-based compression (velocity-bunching), which shortens the bunch and imprints an energy chirp on it. The second stage is performed in a non-isochronous dogleg line, where the compression is completed resulting in a final bunch duration below 90 fs (rms). At the same time, the beam arrival timing-jitter with respect to the PC laser has been measured to be lower than 20 fs (rms). The reported results have been validated with numerical simulations.